DNAJC12 and dopa-responsive nonprogressive parkinsonism - Straniero, L; Guella, I; Cilia, R; Parkkinen, L; Rimoldi, V; Young, A; Asselta, R; Soldà, G; Sossi, V; Stoessl, A; Priori, A; Nishioka, K; et al. (Wiley, 2017)
Biallelic DNAJC12 mutations were described in children with hyperphenylalaninemia, neurodevelopmental delay, and dystonia. We identified DNAJC12 homozygous null variants (c.187A>T;p.K63* and c.79-2A>G;p.V27Wfs*14) in two kindreds with early-onset parkinsonism. Both probands had mild intellectual disability, mild nonprogressive, motor symptoms, sustained benefit from small dose of levodopa, and substantial worsening of symptoms after levodopa discontinuation. Neuropathology (Proband-A) revealed no alpha-synuclein pathology, and substantia nigra depigmentation with moderate cell loss. DNAJC12 transcripts were reduced in both patients. Our results suggest that DNAJC12 mutations (absent in 500 early-onset patients with Parkinson's disease) rarely cause dopa-responsive nonprogressive parkinsonism in adulthood, but broaden the clinical spectrum of DNAJC12 deficiency.